Reconstructing the Curriculum of Love: Perspective of Modern Islamic Education Philosophy - Minhah Makhzuniyah; Ahmad Suhaimi; Achmad Yusuf; Ida Faridatul Hasanah; Donna Tihnike; Saodat Khamidovna Gayupova (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study reconstructs the Curriculum of Love within Modern Islamic Philosophy of Education to counter the cognitive-centric focus of contemporary Islamic education, which neglects affective and spiritual growth and departs from the holistic ideal of insan kamil. Employing qualitative library research and philosophical inquiry, it integrates the work of classical thinkers (Al-Ghazali, Ibn Miskawayh) with modern perspectives (Al-Attas, Nasr) and humanistic pedagogy. The Curriculum of Love, a core pedagogical principle, comprises four domains: love for God (spirituality), love for humanity (social empathy), love for knowledge (intellectual curiosity), and love for nature (ecological stewardship). It unifies tarbiyah, ta’dib, and ta’lim, with love balancing reason and spiritual insight. Theoretically, it offers a humanistic-spiritual paradigm bridging tradition and modern demands. Practically, it provides a strategic blueprint for Islamic schools to design inclusive, character-focused curricula that enhance psychological well-being, foster empathy, and promote social harmony. Love thus becomes the transformative axis aligning intellectual growth with spiritual depth to realize insan kamil and cultivate balanced, empathetic, ecologically conscious individuals.